Large-scale egg-dumping by island nesting Greylag Geese Anser anser: an indication of density-dependent regulation in a breeding population in northwest Lower Saxony, Germany? - Kruckenberg, Helmut (Wildfowl, 2019)
Large egg dumps of more than 100 eggs were observed on an island with colonial-breeding Greylag Geese Anser anser during an aerial survey in 2012. Observations made during subsequent visits to the island found extremely high goose breeding densities with low hatching success. These observations are discussed in relation to studies of density dependence in Greylag Geese and other goose species.